Quality Management Maturity and Its Relationship with Human Resource Development Strategies in Manufacturing Industry - Rosnah, M. Y.; Wan Nurul Karimah, W. A.; Zulkifli, N. (Applied Science and Engineering Progress, 2013)
The relationship between quality management maturity and human resource development strategies in manufacturing industries provide the understanding how organizations shape their human resources to realize their quality goals. In this study, data were obtained from manufacturing companies with at least 3 years experience in quality management implementation. The result of hypothesis testing indicated that there is a positive relationship between quality maturity and human resource development strategies. Based on the results, it can be concluded that as an organization’s maturity in quality management implementation increases, the human resource development strategies in the organization can be expected to become more comprehensive.